(untitled) (Journal of Pharmaceutical Negative Results, 2012)
Objective: To assess the diuretic potential of hot water extract (HWE) of a whole plantof Amaranthus viridis L. Materials and Methods: Different doses (25, 50, and 100 mg/ kg) of HWE of the whole plant of A. viridis or vehicle or furosemide, reference drug,was orally administered to hydrated rats (n = six / group) and their cumulative urineoutput was monitored at hourly intervals for five hours. Result: The HWE of A.viridisdoes not possess significant (P > 0.05) diuretic activity. Conclusion: The HWE ofthe whole plant of A. viridis did not possess diuretic activity in rats, as was claimed intraditional and folkloric medicine.